Draft genome sequence of Desulfoplanes formicivorans Pf12B(T), a sulfate-reducing bacterium of the family Desulfomicrobiaceae - Watanabe, Miho (Stand Genomic Sci, 2017)
Desulfoplanes formicivorans strain Pf12B(T) is the type strain of the type species in the genus Desulfoplanes, which is the one of the genera in the family Desulfomicrobiaceae within the order Desulfovibrionales. This deltaproteobacterium was isolated from a blackish meromictic lake sediment. D. formicivorans strain Pf12B(T) is a Gram-negative, motile and sulfate-reducing bacterium. Cells of strain Pf12B(T) are characterized by possession of vibroid morphology and red fluorescent pigment. Here we describe the features, draft genome sequence and annotation of this organism, the sole species of the genus Desulfoplanes. The genome comprised 3,000,979 bp, 2,657 protein-coding genes and 58 RNA genes.